THE ASSOCIATION BETWEEN SELECTION'S ASSESSMENT ITEMS AND RESIDENT'S PERFORMANCES IN THE OPHTHALMOLOGY DEPARTMENT OF A FACULTY OF MEDICINE - Syntia Nusanti; Anwar Jusuf; Aria Kekalih (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2020)
Background: The admission of residency program in the Ophthalmology Department, FKUI–RSCM is based on the accumulative score from some of the selection's assessment items. The coordinator expects the candidates who received high marks on selection process would also give excellent performance during the residency and therefore the resident would graduate as a qualified ophthalmologist. The aim of this study is to know the association between selection's assessment items and the performance during the residency program.Methods: This was a retrospective cross-sectional study using secondary data. The inclusion criteria were all ophthalmology residents with complete data information of selection, during, and at the end of the residency program from 1999 to 2006, in which results in 101 subjects. The selection data collection includes gender, age, the medical faculty origin, interview result, psychological test result, the entrance examination result, and the selection result. Data during the residency program involve the result from each end of the program's step, result of national examination, and difficulties encountered during the residency program. And lastly, data at the end of the residency program are the GPA and the duration of the residency.Results: There was a significant correlation between the residents' medical faculty origin and their results at the end of each step (p=0.004). There were also significant correlations between age (p=0.004), medical faculty origin (p=0.008), selection result (p=0.002) and their final GPA. Gender also have a significant correlation with difficulties encountered during the residency program (p=0.001). No significant correlation found between selection’s assessment items and duration of the residency.Conclusion: There were some significant correlations between some selection's criteria and the performance of ophthalmology residency program's participants. The medical faculty origin was found to be the strongest predictor to predict the performance of the residents.